What do adults with ASD desire in their residence?. Issue 1 (16th March 2015) - Selcer, Anne; Karlsen, Megan; Mitchell, Jordan; Decker, Phillip J; Durand, Roger
Abstract : Purpose: – Currently, approximately one in 100 Americans meet the criteria for an autism spectrum disorder (ASD) diagnosis. Males are four-to-five times more likely to be diagnosed than females. Because the demand for ADS community-based services outweigh available resources, applicants are placed on a waiting list until services are available. Some wait for years; many adults with an ASD continue to live with their parents who also often serve as de facto case managers. When the decision of which facility to place a resident comes, most families are unprepared to make the decision. The paper aims to discuss these issues. Design/methodology/approach: – Community-based participatory research theory was used in designing interviews of family members facing residential facility placement decisions. Ten interviews were conducted with families. Findings: – Participant answers were categorized within the topic areas of: physical site, staff, transportation, community, diet, behavior, medical, and faith. Research limitations/implications: – Individuals with ASD and their families have varied answers as to what they desire in a residential facility. The most important factor, however, is that the questions be asked, that they be listened to and be given choices on what residence fits their own particular needs. Originality/value: – This study determined what is important to the families of and individuals with intellectual and mental disabilities and autism when looking for community-based placement.